STRATEGI MANAJEMEN SDM PENDIDIKAN DALAM MENGHADAPI KEBIJAKAN WORK FROM HOME (WFH) - Yunika Komalasari; Ricky Firmansyah; Srie Wijaya Kesuma Dewi (STKIP Pesisir Selatan, 2026)
Objective: This study aims to comprehensively examine human resource management (HRM) strategies in the education sector in response to the Work From Home (WFH) policy and to identify the major challenges faced by educational institutions in managing human resources within flexible working systems. Methods: This study employed a Systematic Literature Review (SLR) using the PRISMA approach to identify, screen, evaluate, and synthesize relevant scientific articles published within the last five years. Data were collected from reputable academic databases and analyzed thematically to identify research trends, patterns, and gaps related to educational HRM during the implementation of WFH policies. Results: The findings indicate that: (1) the implementation of WFH has generated various challenges in educational HRM, particularly in planning, coordination, supervision, communication, and performance evaluation. (2) Limitations in technological infrastructure, inadequate digital competence, and communication barriers significantly affected educators’ work effectiveness. (3) The study also reveals psychosocial pressures, including stress, burnout, and work-life imbalance, which negatively impact productivity and employee well-being. Novelty: This study provides a comprehensive synthesis of educational HRM strategies and challenges in the WFH context through the SLR-PRISMA approach, which remains rarely applied in similar studies.